Ancaman keanekaragaman hayati (Biodiversity) terhadap ekosistem daerah penangkapan pukat hela - Fauzan Ramadan; Farhan Ramdhani; Deni Efizon; Nofrizal Nofrizal (Dinamika Lingkungan Indonesia, 2020)
Trawl has the size a mesh size  a small size pockets of the cod end. This allows the trawl fishing gear to potentially be a fishing gear that is not selective about the size of the fish and the species that are targeted for its catch. If this fishing gear is left, its existence will eventually have a negative impact on the sustainability of fish resources, especially in coastal waters. The purpose of this study is to calculate the composition and proportion of main catches, bycatch and discarded catches. It is expected that knowing the composition and proportion of the main, by-product and discarded catches can provide an overview of the pressure on stocks and sustainability of fisheries resources in the waters where trawl is operated. The method used in this study is a survey method. A series of survey activities were carried out directly in the field to identify and count the types of species caught by trawlers. Based on the percentage of main catch, by-catch and discard per type, it Matuta planipes are the dominant species caught by trawlers (23.65%). The main catch Parapenaeus longirostris 15.92%. In addition, the main catch caught were Parapenaeopsis sculptilis (9.787%), Penaeus merguiensis (0.646%), Metapenaeus brevicornis (10.118%), Penaeus indicus (0.029%) and Squilla mantis (0.153%). Percentage of bycatch reaches 2.245% of 10 species caught and discarded catches reach 61.103% of 25 species caught.